APPLICATION OF LOOP MEDIATED ISOTHERMAL AMPLIFICATION (LAMP) AND POLYMERASE CHAIN REACTION (PCR) METHODS FOR DETECTING WILD BOARS, CHICKEN AND BEEF MEAT IN BEEF MEATBALL - WATI - NIM: 21115011 , LINDA
Meatball is a popular food in Indonesia. Meatball producers occasionally mix wild boar meat into meatball, because the price of beef is much higher than wild boar. Indonesia has several wild boar specieses distributed all over Indonesian island, including Java and Sumatera. Valid information about the content of beef in meatball is essential to fulfill consumer right. Consequently, we need to develop an easy and valid method in order to detect pork and wild boar meat in product such as meatball. Loop Mediated Isothermal Amplification (LAMP) is a fast and simple method of testing the content of wild boar in meatballs. In this study, three pairs of primers had been designed using Cytochrome Oxidase Subunit I and Cytochrome b gene that were tested for specificity in DNA of Sus scrofa, Sus barbatus, Sus scrofa domesticus, Bos indicus, Bos taurus, Capra hircus, Rattus argentiventer, Rattus norvegicus, Mus musculus, dan Gallus gallus domesticus. COI primers not only could detect wild boars (Sus scrofa and Sus barbatus) but also pork (Sus scrofa domesticus). On the other hands, cytochrome b primers spesificly amplified DNA of Sus barbatus. However, the result using in this method were inconsistent. Therefore, Multiplex Polymerase Chain Reaction (PCR) method was developed using newly designed primers targeting Cytochrome Oxidase subunit I region, Cytochrome b and D-loop. COI Primers were designed specific for pork and wild boar, D-loop for beef, while cyt b primers designed were spesific for chicken. Primers developed from COI gene could detect the presence of 0,1% wild boar and pork in meatballs (99,9% beef) using 100 ng/Ã‚Âµl DNA total. After three repetitions, PCR was more consistent than the LAMP method. So, it could be concluded that PCR was more accurate than LAMP. Unlike previous studies that only detects Sus scrofa, COI primers in this study could amplify not only Sus scrofa but also Sus barbatus in meatball. Unfortunately, these primers could not distinguish between wild boar and pork. Based on sampling results of meatball that have been done in several points in Java Island by using PCR method, there was one meatball containing a mix of pork or wild boar and chicken. From 161 sample of meatballs were taken from Java Island, mostly the meatballs contain the mixture of beef and chicken (71 sample), 49 sample contain chicken and only 20 sample contain only beef. So, it could be concluded that all of these primers could be applicated to detect the content of pork, wild boar, chicken and beef in meatballs. Keywords: Meatball, Chicken, LAMP, Multiplex PCR, Sus barbatus, Sus scrofa, Java Island.